SAT0107 Interest of a Systematic Screening of Comorbidities in Chronic Inflammatory Rheumatisms. (9th June 2015) - Daien, C.I.; Tubery, A.; Fesler, P.; Du Cailar, G.; Morel, J.; Bousquet, J.; Combe, B.
Abstract : Background: Patients with inflammatory rheumatisms especially rheumatoid arthritis (RA) have a greater risk of cardiovascular events, infections, lung diseases and osteoporosis. European League Against Rheumatisms (EULAR) recommends annual evaluation of the cardiovascular risks. Objectives: A program of comorbidity screening in chronic diseases was set up in Languedoc-Roussillon (MACVIA-LR) as part of the European Innovation Partnership on Active and Healthy Ageing (EIP-AHA). Chronic inflammatory rheumatisms are one of the target diseases. Methods: This screening was set up in a daily clinic of our Rheumatology department. The assessment includes 1) rheumatism evaluation by doctors, nurses and physiotherapists; 2) cardiovascular evaluation including clinical examination, blood tests, modified systematic coronary risk evaluation (mSCORE) calculation, vessel ultrasound and echocardiography, 3) lung evaluation including self-questionnaires, spirometry ± chest X-ray; 4) osteoporosis including bone mineral density and FRAX calculation, and 5) check-up of vaccinal status and the recommended neoplasic screenings. Results: 92 patients already benefited from this systematic screening with 83% (n=76) of RA, 11% (n=10) of spondyloarthritis, 3% (n=2) of psoriatic arthritis and 4% (n=4) of other diseases. The mean rheumatism duration was 14±9 years, the mean age was 59±11 years and 64% were women. Thus, 25.3% and 20% of the patients were obese or overweight, respectively; 27.5% were active smokers and 21.7% were already treated for arterial hypertension. 59.8% of the patients received physiotherapy or occupational therapy advise for the management of their rheumatism. Hypertension was diagnosed in 8.7% (n=8) of the patients; dyslipidemia in 9.8% (n=9); diabetes in 6.5% (n=6) of the patients. The echocardiography showed significant abnormalities (valvular and hypokinesia) in 9% (n=8) of the patients, a significant supra-aortic vessel stenosis was found in 4.5% (n=4) of the population and an abdominal aortic aneuvrysm was diagnosed in 5.7% (n=5). Among 92 patients, 18.4% (n=14) were estimated at high risk of lethal cardiovascular event with a mSCORE≥5 and 27.5% (n=25) patients were sent to a cardiologist to pursue further cardiovascular investigations. Among these, 8 had a myocardial scintigraphy and all were normal. Moreover, 32.6% (n=30) of the patients were estimated at risk of chronic obstructive pulmonary disease or sleep apnea syndrome and were recommended to consult pneumologist. An anti-osteoporosis drug was introduced in 12% (n=11) of the patients. The update of the vaccinations and the neoplasic screenings were prescribed for respectively 52.7% (n=48) and 35.2% (n=32) of the patients. Conclusions: A daily hospitalization for comorbidity screening seems worthy with significant abnormalities such as hypertension, diabetes, dyslipidemia or osteoporosis to treat discovered in 36.2% of the patients. Further investigations were recommended in 50% of the patients. Patient' satisfaction and the effective impact of the proposed or prescribed measures during this screening are under evaluation. Disclosure of Interest: None declared